Design of Microservices - Kirichok, Olena; Feuerlicht, Jiří; Máša, Petr; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
In today's fast-paced software development world, microservices architecture has become a hot topic, offering new possibilities for designing complex systems. This master's thesis dives into microservices design, driven by the author's curiosity and desire to understand how modern software is built. Coming from a background working with traditional monolithic systems, the author is eager to explore the differences between these systems and the more agile microservices approach. The author's hands-on experience with microservices provides a practical perspective and a deep understanding of the challenges and benefits of this approach. By studying how services are broken down, how interfaces are designed, and how systems communicate, the author aims to provide practical insights for software developers. Through a mix of research and hands-on experiments, this thesis aims to demystify the complexities of microservices design. It offers guidance for those looking to adopt this approach in their projects. By sharing lessons learned and best practices, the author hopes to empower others in the software development community to embrace the benefits of microservices architecture. As technology evolves, this thesis serves as a roadmap for navigating the exciting world of microservices, helping developers build more flexible and scalable software systems. By distilling complex concepts into actionable advice, this research aims to make the journey into microservices design less daunting and more rewarding.
Vedoucí práce: Jiří Feuerlicht
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: znalostní a webové technologie [obor dipl. práce]; diplomové práce; master's theses